Clinical Profile of Patients Presenting with Carcinoma Stomach in North-East District of Bangladesh - Das, Aparna; Saha, Modhusudan; Shil, Bimal Chandra; Yasmin, Rubina; Banik, Gobinda; Salam, Mahjuba Umme; Minnat, Baharul (Journal of Medicine, 2014)
Background: The pattern and incidence of Carcinoma Stomach vary widely in different parts of the world. Overall it is the 2nd most common cause of death but in some Asian countries, it is still the commonest cause of cancer death in patients of > 50 years. Aim: To analyze the clinical presentation and histological findings of patients of carcinoma of the stomach. Methods and materials: This study was done over a period of 2 years between January 2011 and December 2012. Adult patients (Age more than 18 years) of histologically confirmed as having carcinoma stomach were included in the study. Studied variables included age, gender, socioeconomic status, clinical presentations, site of lesion, histopathological subtypes. Diagnostic modalities included abdominal ultrasound, upper GI (gastrointestinal) endoscopy and endoscopic biopsy to confirm the diagnosis. Results: Total number of patients included in this study was 150. The number of patients in <50 years age group and >50 years age group were 50 (33.33%) & 100 (66.66%) respectively. The median age at presentation was 57 years. The peak incidence was in 61-70 years age group. In our study,male: female ratio being 2.3:1. By occupation, farmer 74 (49%), housewife 37(24.6%), serviceholder12(8%), business man 5(10%) and others12 (8%). 71 (47.4%) patients were from lower socioeconomic group, middle74 (49.4%), upper class 5 (3.4%) & only 63 (42%) were literate. The common clinical features were vomiting 28%, abdominal pain 18%, weight loss and anorexia 17.3% , dyspepsia 16% , Anaemia (26% ), Abdominal mass 4%, Metastatic lymph node 4%, Ascites 1.3%. lesions are involved in Cardia 14%, Body &Antrum 6.6%, Antrum 2.6%, Body 23.3%, Fundus 2% and Diffusely in 1.3% cases. Conclusion: As regards to clinical presentation, patients in our country are presenting more with features of gastric outlet obstruction whereas abdominal lump and upper GI bleeding are more common in Western world. If gastric carcinoma is diagnosed at an early stage, patients can have a highly favorable prognosis. DOI: http://dx.doi.org/10.3329/jom.v15i2.20683 J MEDICINE 2014; 15 : 118-121